DALILA IN MILTON’S SAMSON AGONISTES - Dohal, Gassim H. (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2022)
For several reasons, Delilah’s scene in John Milton’s Samson Agonistes is crucial to this tragedy. First of all, she plays the "tempter" in this drama. Second, she could be compared to many characters in other dramas, such as Eve, Satan, and other notable figures. Finally, the length of her episode suggests that she is in the midst of tragedy; she adds and helps represent Samson’s growth as a character. Finally, Delilah awakens and helps Samson understand his flaws and weaknesses, after which she finds the right path and accepts his fate.